Long-term Safety and Efficacy of Efgartigimod in Patients With Generalized Myasthenia Gravis: Interim Results of the ADAPT+ Study. (5th December 2022) - Howard, James; Bril, Vera; Vu, Tuan; Karam, Chafic; Peric, Stojan; De Bleecker, Jan; Murai, Hiroyuki; Meisel, Andreas; Beydoun, Said; Pasnoor, Mamatha; Guglietta, Antonio; Ulrichts, Peter; et al.
Abstract : Objective: To evaluate the safety and efficacy of efgartigimod in patients with generalized myasthenia gravis (MG) enrolled in the ADAPT+ long-term extension study. Background: Treatment with efgartigimod, a human IgG1 antibody Fc-fragment that blocks neonatal Fc receptor, resulted in clinically meaningful improvement (CMI) in MG-specific outcome measures in the ADAPT phase 3 clinical trial. All patients who completed ADAPT were eligible to enroll in its ongoing open-label, 3-year extension study, ADAPT+. Design/Methods: Efgartigimod (10 mg/kg IV) was administered in cycles of once-weekly infusions for 4 weeks, with subsequent cycles initiated based on clinical evaluation. Efficacy was assessed during each cycle utilizing Myasthenia Gravis Activities of Daily Living (MG-ADL) and Quantitative Myasthenia Gravis (QMG) scales. Results: Ninety-one percent of ADAPT patients (151/167) entered ADAPT+. As of February 2021, 106 AChR-Ab+ and 33 AChR-Ab– patients had received at least 1 dose of open-label efgartigimod (including 66 ADAPT placebo [PBO] patients). The mean (SD) study duration was 363 (114) days, resulting in 138 patient-years of observation. Similar incidence rates per patient year (IR/PY) of serious adverse events were seen in ADAPT (efgartigimod: 0.11; placebo: 0.29) compared to ADAPT+ (0.25). Five deaths (acute myocardial infarction, COVID-19 pneumonia/septic shock, bacterial pneumonia/MG crisis, malignant lung neoplasm, and unknown [multiple cardiovascular risk factors identified on autopsy]) occurred; none were considered related to efgartigimod by the investigator. AEs were predominantly mild or moderate. CMI was observed in AChR-Ab+ patients during each cycle (up to 10 cycles) at magnitudes comparable to improvements observed at week 3 of cycle 1 (mean[SE] improvements: MG-ADL, –5.1[0.34]; QMG, –4.7[0.41]). Clinical improvements mirrored maximal reductions in total IgG and AChR-Abs across all cycles. Conclusions: This analysis suggests the efficacy of long-term treatment with efgartigimod was consistent across multiple cycles. No new safety signals were identified, despite being conducted before vaccine availability during the COVID-19 pandemic.